Representation of Iran among Iraqi social media users (A case study of Facebook users after the defeat of ISIS until the martyrdom of Hajj Qassem Soleimani) - mohsen finizadeh bidgoli (رهیافتهای سیاسی و بین المللی)
Extended AbstractIntroduction and Objectives:The nature and essence of power have varied across historical eras, shaped by social, cultural, political, and technological structures. In classical, modern, and postmodern periods, power has taken on different definitions and manifestations. However, in today's world—and likely in the future—soft power and public diplomacy offer some of the most relevant frameworks for understanding power’s current form and function. At the same time, the growing importance of social networks has become an undeniable reality. These platforms provide a valuable source of insight into public opinion on a wide range of subjects, from political figures and national policies to foreign relations and cultural perceptions. Given Iraq's geographic proximity, deep religious and cultural ties with Iran, and its potential as both a strategic partner and a major market, understanding Iraqi public sentiment toward Iran is more vital than ever. Factors such as Iran’s military advisory presence in Iraq, its role in the defeat of ISIS, long-standing support for Iraqi resistance groups, and the presence of shared religious sites underscore the importance of analyzing Iraqi societal attitudes toward Iran. In this context, the representation of Iran’s image among Iraqi users on social media—particularly on Facebook, which remains the dominant platform in Iraq—can serve as a meaningful indicator of the success of Iran’s soft power and public diplomacy efforts.Method: This research focuses on the representation of Iran among Iraqi social media users, with Facebook as the primary source of data due to its widespread use in Iraq. Data was collected, cleaned, stored, and processed using computer-based systems. The study employed thematic analysis to examine content posted by Iraqi Facebook users from the period following the defeat of ISIS up to the martyrdom of General Qassem Soleimani. The data was analyzed on a yearly basis to track evolving trends and sentiments.Discussion and Result:The research identified and categorized the main topics related to Iran from 2018 to 2020 into fourteen primary themes. These include: - Groups aligned with the Islamic Revolution. - Political relations between Iran and Iraq. - Commentary on Iranian religious and social culture. - Content related to the Sacred Defense and the Iran-Iraq War. - Economic relations and Iranian products. - Allegations of Iranian interference in Iraqi elections and governance. - Sports-related topics between the two nations. - Bilateral news coverage. - U.S. sanctions on Iran and Iraq's role. -Representations of Iranian political and military figures (e.g., the Supreme Leader, the President, General Soleimani). - The Arbaeen pilgrimage and the presence of Iranians during the procession. These themes provide a multifaceted view of Iran’s image on Iraqi social media platforms.Conclusion: The image of Iran among Iraqi Facebook users faces significant challenges. Despite Iran’s military assistance in the fight against ISIS and the sacrifices made—such as the martyrdom of Iranian youth and military commanders to ensure Iraq’s security—these contributions receive limited visibility in online Iraqi discourse. Figures like General Soleimani, who played a key role in these efforts, are not consistently portrayed as heroes or mythic figures in Iraqi social media narratives. Moreover, Iranian products lack strong visibility and support in terms of advertising volume and consumer engagement among Iraqi users. Overall, the data suggests that Iran’s soft power has not translated effectively into positive public sentiment in Iraq during the studied period. Strategic efforts in public diplomacy and targeted media engagement may be necessary to reshape and enhance Iran's image in Iraqi society.